2007
DOI: 10.1038/sj.eye.6702995
|View full text |Cite
|
Sign up to set email alerts
|

Mean intraocular pressure and progression based on corneal thickness in patients with ocular hypertension

Abstract: Purpose To determine the incidence of glaucomatous progression at mean intraocular pressure (IOP) levels in patients with ocular hypertension (OHT). Methods A retrospective, multicentre, cohort analysis of 230 OHT patients with 5 years of follow-up evaluated for risk factors associated with progressive optic disc and visual field loss to determine the incidence of glaucomatous progression. Results Forty percent of patients with IOPs X24 mmHg, 18% of patients with IOPs of 21-23 mmHg, 11% of patients with IOPs w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
13
0
2

Year Published

2008
2008
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 16 publications
0
13
0
2
Order By: Relevance
“…P eak intraocular pressure (IOP) has recently been evaluated as being a potential risk factor for long-term glaucomatous progression for which there are several general lines of supportive evidence: first, Stewart and associates have shown in 2 studies that long-term, 5-year peak pressure was an independent risk factor; and second, the Advanced Glaucoma Intervention Study (AGIS) showed a peak pressure of £ 18 mmHg, associated with a mean pressure of 12.8 mmHg, to be the best combination to prevent progression, although the independence of the peak pressure was not evaluated. [1][2][3] Despite these findings, there is not uniform acceptance regarding the importance of the peak pressure within the ophthalmic community. This is because, at least in part, not all studies have shown peak pressure to be an independent risk factor.…”
Section: Introductionmentioning
confidence: 99%
“…P eak intraocular pressure (IOP) has recently been evaluated as being a potential risk factor for long-term glaucomatous progression for which there are several general lines of supportive evidence: first, Stewart and associates have shown in 2 studies that long-term, 5-year peak pressure was an independent risk factor; and second, the Advanced Glaucoma Intervention Study (AGIS) showed a peak pressure of £ 18 mmHg, associated with a mean pressure of 12.8 mmHg, to be the best combination to prevent progression, although the independence of the peak pressure was not evaluated. [1][2][3] Despite these findings, there is not uniform acceptance regarding the importance of the peak pressure within the ophthalmic community. This is because, at least in part, not all studies have shown peak pressure to be an independent risk factor.…”
Section: Introductionmentioning
confidence: 99%
“…It is helpful in the differentiation of ocular hypertension, normal tension glaucoma, and chronic open-angle glaucoma. 3 Furthermore, it is an important basic parameter in the planning of laser refractive surgery. For laser-assisted in situ keratomileusis or photorefractive keratectomy, the remaining postoperative residual corneal thickness is an important prognostic factor to guarantee the stability of the surgically altered corneal architecture.…”
mentioning
confidence: 99%
“…Several studies have evaluated the role of IOP variation during the day as a risk factor for glaucoma progression,3 4 and considerable interest has been directed towards this topic in the recent years 57. Circadian fluctuation in ocular perfusion pressure (OPP) also appears to be an independent risk factor for POAG and normal tension glaucoma 810…”
mentioning
confidence: 99%